Cementless Total Knee Arthroplasty in Patients Older Than 75 Years - Newman, Jared M.; Khlopas, Anton; Chughtai, Morad; Gwam, Chukwuweike U.; Mistry, Jaydev B.; Yakubek, George A.; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2017)
Some surgeons have been hesitant to use cementless fixation for total knee arthroplasty (TKA) in elderly patients due to concerns regarding successful bone biological fixation. Therefore, this study evaluated: (1) implant survivorship, (2) functional outcomes, (3) radiographic outcomes, and (4) complications in patients over 75 years of age who underwent cementless total knee arthroplasty. A total of 134 patients (142 TKAs) older than 75 years at a single institution between June 2008 and June 2014 were retrospectively reviewed. Their mean follow-up was 4 years (range: 2–8 years). The cohort consisted of 91 women and 43 men who had a mean age of 80 years (range: 76 to 88 years). The preoperative diagnoses were osteoarthritis (n = 107 patients), rheumatoid arthritis (n = 21 patients), and osteonecrosis (n = 6 patients). Descriptive statistics were used to calculate the means and ranges and a Kaplan-Meier analysis was performed to determine the aseptic and all cause implant survivorship. Radiographic evaluation was performed using the new Knee Society Radiographic Evaluation and Scoring System. Functional outcomes at the final follow-up as well as all medical and surgical complications were recorded for each patient. The aseptic implant survivorship was 99.3% (95% CI: 7.9–8.1), and the all cause implant survivorship was 98.6% (95% CI: 7.9–8.1). There was one aseptic revision and one septic revision. At the latest follow-up the mean Knee Society pain score was 93 points (range, 80–100 points), and the mean Knee Society function score was 84 points (range, 70–90 points). On radiographic evaluation, there were no progressive radiolucencies, subsidence, and loosening of prostheses at the latest follow-up. The use of cementless TKA demonstrated excellent survivorship, mid-term clinical and functional outcomes, as well as no progressive radiolucencies or subsidence in patients older than 75 years. In addition, there was a low rate of surgical and medical complications. Therefore, cementless TKA may be a good option for patients older than 75 years.
Keywords: total knee arthroplasty; cementless; elderly; survivorship; outcomes